HYGIENIC ASSESSMENT OF THE IMPACT OF AIR POLLUTION IN RESIDENTIAL AREAS ON POPULATION HEALTH - Salomova F. I.; Sharafatdinova A. A. (Web of Journals Publishing, 2026)
Air pollution in residential areas is considered one of the main ecological and hygienic factors that directly and indirectly affect public health under modern urbanization conditions. This literature review provides a systematic analysis of scientific studies on the health effects of major atmospheric pollutants commonly found in residential areas, including fine particulate matter (PM2.5 and PM10), nitrogen dioxide (NO₂), sulfur dioxide (SO₂), carbon monoxide (CO), ozone (O₃), and volatile organic compounds. Based on data from the World Health Organization (WHO) and other international research centers, the role of air pollution in the development of respiratory, cardiovascular, allergic, and oncological diseases is assessed from a hygienic perspective. The results of the review substantiate the necessity of developing preventive and sanitary-hygienic measures aimed at improving air quality in residential areas.
Keywords: Air pollution, residential areas, population health, hygienic assessment, ambient air, PM2.5, PM10, cardiovascular diseases.